The Shale Boom and Family Structure: Oil and Gas Employment Growth Relationship to Marriage, Divorce, and Cohabitation. (9th October 2019) - Shepard, Michael; Betz, Michael; Snyder, Anastasia
Abstract: Shale oil and gas extraction technology has caused a large shift in the United States' energy landscape over the last decade. This had a wide range of impacts on rural communities mostly in which oil and gas extraction occurs. While many studies have focused on the economic and environmental impact of shale development, researchers have only begun to study the social changes brought on by the shale resource extraction. We examine the influence of shale oil and gas employment as a share of overall county employment on county marriage, divorce, and cohabitation rates. We find evidence that oil and gas employment growth is associated with decreased marriage rates and increased divorce rates from 2009 to 2014. We test several channels through which oil and gas development may influence marriage behaviors and find that changes in female labor force participation, county sex ratios, and median household incomes are associated with oil and gas development. We also test for differences across the rural/urban continuum and find that our results are largely driven by nonmetro counties.